The K346T mutant of GnT-III bearing weak in vitro and potent intracellular activity - Hashimoto, Yuta; Kawade, Haruka; Bao, WanXue; Morii, Sayaka; Nakano, Miyako; Nagae, Masamichi; Murakami, Reiko; Tokoro, Yuko; Nakashima, Misaki; Cai, Zixuan; Isaji, Tomoya; Gu, Jianguo; et al. (Biochimica et biophysica acta. General subjects, 2024)
N-Acetylglucosaminyltransferase-III (GnT-III, also designated MGAT3) catalyzes the formation of a specific N-glycan branch, bisecting GlcNAc, in the Golgi apparatus. Bisecting GlcNAc is a key residue that suppresses N-glycan maturation and is associated with the pathogenesis of cancer and Alzheimer's disease. However, it remains unclear how GnT-III recognizes its substrates and how GnT-III activity is regulated in cells. Using AlphaFold2 and structural comparisons, we predicted the key amino acid residues in GnT-III that interact with substrates in the catalytic pocket. We also performed in vitro activity assay, lectin blotting analysis and N-glycomic analysis using point mutants to assess their activity. Our data suggested that E320 of human GnT-III is the catalytic center. More interestingly, we found a unique mutant, K346T, that exhibited lower in vitro activity and higher intracellular activity than wild-type GnT-III. The enzyme assays using various substrates showed that the substrate specificity of K346T was unchanged, whereas cycloheximide chase experiments revealed that the K346T mutant has a slightly shorter half-life, suggesting that the mutant is unstable possibly due to a partial misfolding. Furthermore, TurboID-based proximity labeling showed that the localization of the K346T mutant is shifted slightly to the cis side of the Golgi, probably allowing for prior action to competing galactosyltransferases. The slight difference in K346T localization may be responsible for the higher biosynthetic activity despite the reduced activity. Our findings underscore the importance of fine intra-Golgi localization and reaction orders of glycosyltransferases for the biosynthesis of complex glycan structures in cells. •GnT-III biosynthesizes a unique N-glycan branch, bisecting GlcNAc.•The catalytic center of GnT-III was predicted by structural comparison.•A GnT-III mutant K346T was found showing the higher intracellular activity.•A slight shift in localization of K346T was suggested.